CREATING PERSONALIZED LEARNING PATHWAYS THROUGH ARTIFICIAL INTELLIGENCE: A COMPREHENSIVE STUDY - Xatamova Sojida Sobir qizi; Jo‘rayev Muhammadrahimxon Murod o‘g‘li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  this  paper  explores  the  growing  role  of  artificial  intelligence  in shaping  modern  education  through  the  development  of  personalized  learning pathways. Traditional instructional models often assume that all learners progress at the same pace and possess similar abilities, which leads to disengagement and uneven learning outcomes. Artificial intelligence introduces adaptive tools that adjust to the learner’s knowledge level, learning speed, and individual characteristics. This study reviews  theoretical  foundations  supporting  personalized  learning,  explains  how  AI systems function within educational environments, and highlights their advantages and challenges. It also addresses ethical considerations and future directions. The analysis demonstrates that while AI has the potential to significantly enhance learner-centered education,  issues  such  as  data  privacy,  algorithmic  bias,  teacher  preparedness,  and equitable access must be carefully managed.